Organic solid waste management in a circular economy perspective – A systematic review and SWOT analysis - Paes, Luis Alberto Bertolucci [UNESP] (2019)
This study carried out a systematic literature review and content analysis to identify the state of the art and the strengths, weaknesses, opportunities, and threats (SWOT analysis) of organic waste management through circular economy (CE) principles and created a research agenda on the topic. The main threats and weaknesses were: logistic cost and supply chain management; seasonality; availability and lack of homogenization of the raw material (organic waste); quality and efficiency of the alternative product, which is not economically competitive with traditional ones; and lack of technical standards and regulation. The main strengths were: the possibility to turn waste streams into valuable resources, contributing to environmental improvement and greenhouse gas emission reduction and costs reduction; stimulation of cooperative projects and production of bio-based chemicals and energy; and job creation and new investment opportunities as the result of the development of a new business model and a new value chain based on organic waste, boosting companies that focus on green solutions. The proposed research agenda concentrated on emerging value chains and modifying existing business models, legislation and taxation to aid in the competitiveness of alternative materials derived from organic waste in a CE perspective.